Chronic ethanol‐mediated hepatocyte apoptosis links to decreased TET1 and 5‐hydroxymethylcytosine formation. Issue 2 (6th September 2018) - Ji, Chengcheng; Nagaoka, Katsuya; Zou, Jing; Casulli, Sarah; Lu, Shaolei; Cao, Kevin Y.; Zhang, Hongyu; Iwagami, Yoshifumi; Carlson, Rolf I.; Brooks, Keri; Lawrence, Jonathan; Mueller, William; et al.
ABSTRACT: The 5‐hydroxymethylcytosine (5hmc) is a newly identified epigenetic modification thought to be regulated by the TET family of proteins. Little information is available about how ethanol consumption may modulate 5hmC formation and alcoholic liver disease (ALD) progression. A rat ALD model was used to study 5hmC in relationship to hepatocyte apoptosis. Human ALD liver samples were also used to validate these findings. It was found that chronic ethanol feeding significantly reduced 5hmC formation in a rat ALD model. There were no significant changes in TET2 and TET3 between the control‐ and ethanol‐fed animals. In contrast, methylcytosine dioxygenase TET1 (TET1) expression was substantially reduced in the ethanol‐fed rats and was accompanied by increased hepatocyte apoptosis. Similarly, knockdown of TET1 in human hepatocyte‐like cells also significantly promoted apoptosis. Down‐regulation of TET1 resulted in elevated expression of the DNA damage marker, suggesting a role for 5hmc in hepatocyte DNA damage as well. Mechanistic studies revealed that inhibition of TET1 promoted apoptotic gene expression. Similarly, targeting TET1 activity by removing cosubstrate promoted apoptosis and DNA damage. Furthermore, treatment with 5‐azacitidine significantly mimics these effects, suggesting that chronic ethanol consumption promotes hepatocyte apoptosis and DNA damage by diminishing TETl‐mediated 5hmC formation and DNA methylation. In summary, the current study provides a novel molecular insight that TETl‐mediated 5hmC is involved in hepatocyte apoptosis in ALD progression.—Ji, C., Nagaoka, K., Zou, J., Casulli, S., Lu, S., Cao, K. Y., Zhang, H., Iwagami, Y., Carlson, R. I., Brooks, K., Lawrence, J., Mueller, W., Wands, J. R., Huang, C.‐K. Chronic ethanol‐mediated hepatocyte apoptosis links to decreased TET1 and 5‐hydroxy‐methylcytosine formation. FASEB J. 33, 1824–1835 (2019). www.fasebj.org